Chiny – ekonomiczny lider regionu czy świata? - Jankowiak, Anna (China – economic partner of the region or of the world?, 2009)
The People’s Republic of China is one of the most important players in the global economy. For many years China has been seen as a factory of the world, but now we are seeing Chinese corporations, and their brands, taking a position in the global economy. Chinese increase in share of world trade over past few years is impressive. The idea of this article is to show the growing role of Chinese economy in Asia and Pacific region and in the whole world
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 328-339